2019
DOI: 10.1007/s11116-019-10017-7
|View full text |Cite
|
Sign up to set email alerts
|

Demand management of congested public transport systems: a conceptual framework and application using smart card data

Abstract: Transportation Demand Management (TDM), long used to reduce car traffic, is receiving attention among public transport operators as a means to reduce congestion in crowded public transportation systems. Though far less studied, a more structured approach to Public Transport Demand Management (PTDM) can help agencies make informed decisions on the combination of PTDM and infrastructure investments that best manage crowding. Automated fare collection (AFC) data, readily available in many public transport agencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…If human mobility flows were perfectly balanced and evenly distributed throughout the day, no such tradeoff would occur—i.e., if for each passenger delivered at a destination, there were another passenger at the same location available for immediate pickup. In practice, however, there is overwhelming literature showing that human flows are highly unbalanced spatially and temporally 35 , 41 43 ; thus, it is important to observe that, unless sharing of rides is considered, the sharing of vehicles cannot directly reduce the total traveled distance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If human mobility flows were perfectly balanced and evenly distributed throughout the day, no such tradeoff would occur—i.e., if for each passenger delivered at a destination, there were another passenger at the same location available for immediate pickup. In practice, however, there is overwhelming literature showing that human flows are highly unbalanced spatially and temporally 35 , 41 43 ; thus, it is important to observe that, unless sharing of rides is considered, the sharing of vehicles cannot directly reduce the total traveled distance.…”
Section: Resultsmentioning
confidence: 99%
“…Second, human mobility is temporally concentrated, particularly in the morning and afternoon peak commute periods 41 43 . Most vehicles will be idle at night, and many during the middle of the day, and require parking.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling traveler responses to peak avoidance policies has been an important focus in these studies. Conventional choice models, such as the multivariate logit model (Ben-Elia & Ettema, 2011a, 2011b), multivariate probit model (Zhang et al, 2014), and binary logit model (Halvorsen et al, 2019) have been used to maximize the utility of choosing peak avoidance by incorporating individual socioeconomic characteristics and mode attributes (Ben-Akiva et al, 1999). However, the naturalistic data sources are typically anonymous and do not have information about the sociodemographic characteristics of the travelers.…”
Section: Modelling Peak-avoidance Behaviormentioning
confidence: 99%
“…Consequently, such models result in 'one size fits all' policy recommendations. However, the homogeneity assumption ignores the fact that there are different types of subway travelers (Zou et al, 2018;Halvorsen et al, 2019), who are likely to have different sensitivities towards the incentives, leading to substantial taste heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Overcrowding is known to be an issue in major transit systems, including the Underground in London, and major systems in Asia like Hong Kong’s MTR and Tokyo’s railways ( 1 , 2 ). In Tokyo, a recent report found that most delays of less than 10 min were caused by passengers ( 3 ).…”
Section: Introductionmentioning
confidence: 99%